Propuesta de un modelo matemático que permita mejorar el desempeño de la cadena logística de abastecimiento del banano en la región del Magdalena (2023)
The supply chain in the Magdalena banana area is a matter of great importance for this department, since poor logistical procedures in both supply and poor agricultural practices affect national and international trade, as well as the producing farms. which could be affected mainly by large material losses for the farmer and large drops in GDP in the area.